I have two related questions on the representation of the momentum operator in the position basis.

The action of the momentum operator on a wave function is to derive it:

$$\hat{p} \psi(x)=-i\hbar\frac{\partial\psi(x)}{\partial x}$$

(1) Is it ok to conclude from this that:

$$\langle x | \hat{p} | x' \rangle = -i \hbar \frac{\partial \delta(x-x')}{\partial x}?$$

And what does this expression mean?

(2) Using the equations:

$$ \frac{\langle x | \hat{x}\hat{p} | x' \rangle}{x} = \frac{\langle x | \hat{p}\hat{x} | x' \rangle}{x'} = \langle x | \hat{p} | x' \rangle $$


$$\langle x | [\hat{x},\hat{p}]|x'\rangle=i\hbar \delta(x-x')$$

one can deduce that

$$\langle x | \hat{p} | x' \rangle = i \hbar \frac{\delta(x-x')}{x-x'}$$

Is this equation ok? Does it follow that

$$\frac{\partial \delta(x-x')}{\partial x} = - \frac{\delta(x-x')}{x-x'}?$$

  • 2
    $\begingroup$ If you like this question you may also enjoy reading this post. $\endgroup$
    – Qmechanic
    Commented Feb 6, 2013 at 22:26
  • 2
    $\begingroup$ Also, be careful with dividing by $x-x'$ since this is only defined when $x\neq x'$. In fact, notice that @Qmechanic is careful to write his identities without ever dividing by $x-x'$. $\endgroup$ Commented Feb 6, 2013 at 22:44
  • $\begingroup$ Thanks for all the answers. See also Ron Maimon's answer here (in the question suggested by @Qmechanic), which pretty much answers my question too. $\endgroup$
    – a06e
    Commented Feb 7, 2013 at 0:17

3 Answers 3


1) Notice that by inserting a complete set of position states we can write $$ \hat p \psi(x) = \langle x|\hat p|\psi\rangle = \int dx'\langle x|\hat p|x'\rangle\langle x'|\psi\rangle =\int dx'\langle x|\hat p|x'\rangle \psi(x') $$ so if we set $$ \langle x|\hat p|x'\rangle = -i\hbar \frac{\partial}{\partial x}\delta(x-x') =i\hbar \frac{\partial}{\partial x'}\delta(x-x') $$ then we can use integration by parts to obtain $$ \hat p \psi(x) =i\hbar \int dx'\frac{\partial}{\partial x'}\delta(x-x') \psi(x') = -i\hbar \int dx'\delta(x-x') \frac{d \psi}{dx'}(x') = -i\hbar \frac{d\psi}{dx}(x) $$ So your expression is correct. The derivative of a delta function is essentially defined by the integration by parts manipulation that I just performed; in fact derivatives of distributions in general are defined in an analogous way. See this lecture for example.

Hope that helps; let me know of any typos!



1) User joshphysics has already correctly answered OP's 1st question.

2a) Concerning OP's 2nd question, one derives

$$i\hbar \delta(x-x^{\prime})~=~i\hbar\langle x | x^{\prime} \rangle ~=~\langle x | [\hat{x},\hat{p}] | x^{\prime} \rangle ~=~\langle x | \hat{x}\hat{p} | x' \rangle-\langle x | \hat{p} \hat{x} | x' \rangle$$ $$\tag{A}~=~(x-x^{\prime})\langle x | \hat{p} | x^{\prime} \rangle ~\stackrel{(1)}{=}~-i\hbar(x-x^{\prime})\frac{\partial}{\partial x}\delta(x-x^{\prime}).$$

In other words,

$$\tag{B}\delta(x-x^{\prime})~=~-(x-x^{\prime})\frac{\partial}{\partial x}\delta(x-x^{\prime}),$$

which also follows by differentiating the identity

$$\tag{C} (x-x^{\prime})\delta(x-x^{\prime})~=~0 $$

wrt. $x$.

2b) Eq. (B) should not be divide on both sides wrt. $x-x^{\prime}$. The problem is essentially that the distribution $\frac{1}{x}\delta(x)$ is ill-defined.

One argument why this is so goes roughly as follows. Recall that one way to make sense of a distribution $u$ is to evaluate on smooth test functions $g:\mathbb{R}\to \mathbb{C}$. For instance, if the distribution $u$ is the Dirac delta distribution, then by definition

$$\tag{D} u[g] ~:= ~g(0), $$

or equivalently, in a perhaps more familiar notation,

$$\tag{E} \int_{\mathbb{R}}\! dx~\delta(x) g(x) ~:= ~g(0). $$

One can in general not multiply$^1$ two distributions, but one can multiply a smooth function $f:\mathbb{R}\to \mathbb{C}$ with a distribution $u$. The product $f\cdot u$ is by definition

$$\tag{F} (f\cdot u)[g] ~:= ~u[fg]. $$

So if $u$ is the Dirac delta distribution, one gets

$$\tag{G} (f\cdot u)[g] ~:= ~f(0) g(0). $$

In OP's case, if we try to set $f(x)=\frac{1}{x}$, then $f(0)$ would be ill-defined.

Another less formal argument is that if we wrongly accept $\frac{1}{x}\delta(x)$ as a distribution, then we are prone to seemingly meaningless contradictions a la

$$x\cdot (\frac{1}{x} \delta(x))~=~x\cdot (\frac{1}{x}\cdot \delta(x))~=~(x\cdot \frac{1}{x})\cdot \delta(x)$$ $$\tag{H}~=~( \frac{1}{x}\cdot x)\cdot \delta(x)~=~ \frac{1}{x}\cdot (x\cdot \delta(x))~=~ \frac{1}{x}\cdot 0~=~0, \quad \text{(Wrong!)} $$

i.e. we have lost associativity of multiplication.


$^1$ We ignore Colombeau theory. See also this mathoverflow post.

  • 1
    $\begingroup$ This extra detail was very nice; I find all of your posts on distributions helpful; thanks Qmechanic. $\endgroup$ Commented Feb 7, 2013 at 2:18

@joshphysics gave an excellent illustration of why your first part, i.e. ⟨x|p^|x′⟩=−iℏ∂δ(x−x′)∂x? is consistent with quantum mechanics;

Let's check your second part rather intuitively.

Since in general:

$$ \int xg(x)f'(x)dx=-\int f(x)\frac{d}{dx}(xg(x))dx=-\int f(x)(xg'(x)+g(x))dx $$ If $$ f(x)=\delta(x) $$ We conclude that:

$$ \int f(x)(xg'(x)+g(x))dx=\int\delta(x)g(x)dx=-\int xg(x)\delta'(x)dx $$


$$ \delta'(x)=-\frac{1}{x}\delta(x) $$

Is true in mathematics


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service and acknowledge you have read our privacy policy.

Not the answer you're looking for? Browse other questions tagged or ask your own question.